Do trustees and administrators matter? Diversifying the faculty across gender lines - Ronald G. Ehrenberg; George H. Jakubson; Mirinda L. Martin; Joyce B. Main; Thomas Eisenberg (Institute for the Study of Labor (IZA), 2009)
Our paper focuses on the role that the gender composition of the leaders of American colleges and universities- trustees, presidents/chancellors, and provosts/academic vice presidents - plays in influencing the rate at which academic institutions diversify their faculty across gender lines. We use institutional level panel data that we have collected for a large sample of American academic institutions. We find that, other factors held constant including our estimate of the expected share of new hires at an institution that should be female, that institutions with female presidents/chancellors and female provosts/academic vice presidents, and those with a greater share of female trustees, increase their share of female faculty at a more rapid rate. The magnitudes of the effects of these leaders are larger at smaller institutions, where central administrators play a larger role in faculty hiring decisions. A critical share of female trustees must be reached before the gender composition of the board matters.
Keywords: J16; J44; I21; 330; Academic institutions; diversifying the faculty; gender; trustees; presidents; provosts; Hochschule; Weibliche Führungskräfte; Frauenpolitik; Gleichberechtigung; USA